A national cross-sectional survey of dental anxiety in the French adult population - Faulks Denise; Collado Valérie; Nicolas Emmanuel; Bullier Brigitte; Hennequin Martine (BMC, 2007)
Abstract Background Dental anxiety is a public health problem but no epidemiological study has been undertaken in France to evaluate its prevalence. The aim of this study was to estimate the prevalence, severity and associations of dental anxiety in a sample of the French adult population. Methods A convenience sample of 2725 adults (mean age = 47 years, SD16, minimum = 16, maximum = 101 years), representative of the French population with regard to age and urban distribution, completed a French version of the Corah Dental Anxiety scale (DAS) and a questionnaire relating to their dental appointments. Results Moderate dental anxiety (14≥DAS≥13) was revealed for 172 persons (6.2%), while 195 (7.3%) had severe dental anxiety (DAS≥15), giving an overall prevalence of dental anxiety of 13.5%. Prevalence was lower proportionally with age (P < 0.001) and was higher in French overseas territories and in the countryside (P < 0.01). Farmers and low skilled workers were significantly more anxious than executives and shopkeepers (P < 0.001). Anxiety was associated with avoidance of care (p < 0.001) and lack of regular dental appointments (p < 0.001). Conclusion Dental anxiety in France appears to concern a similar proportion of the population as in other industrialised European, Australasian or North American countries. Recommendations for prevention and management of dental anxiety are made with reference to dental education and health care services in France.